Can Decision Support Help Patients With Spinal Stenosis Make a Treatment Choice?: A Prospective Study Assessing the Impact of a Patient Decision Aid and Health Coaching. Issue 7 (April 2016) - Kearing, Stephen; Berg, Susan Z.; Lurie, Jon D.
Abstract : Study Design: A prospective, randomized study on patients with lumbar spinal stenosis who received a decision support intervention to facilitate their treatment choice. Objective: The aim of this study was to assess the impact of telephone health coaching (HC) in addition to a video decision aid (DA) compared with a DA alone for patients with spinal stenosis. Summary of Background Data: Treatment options for lumbar spinal stenosis include surgical and nonsurgical approaches. Patient DAs and HC have been shown to help patients make an informed treatment choice consistent with personal preferences. Methods: Eligible patients with spinal stenosis were identified by an orthopedic surgeon or a nonsurgical spine specialist. Consenting participants were randomly assigned to either a video DA or a video DA along with HC (DA + HC). Patients completed baseline and follow-up questionnaires at 2 weeks, and 6 months after the decision support intervention(s). Results: Ninety-eight patients were randomized to the DA + HC group and 101 to the DA-only group; 168 of 199 (84%) patients completed responses at all time points. Both groups showed improved understanding of spinal stenosis treatments and progress in decision making after watching the DA ( P < 0.001). At 2 weeks, more patients in the coaching group had made a treatment decision (DA + HC 74% vs . DA only 52%, P < 0.01). At 6-month follow-up, the uptake of surgery was similar for both groups (DA + HC 21% had surgery vs . DA only 17%); satisfaction with the treatments received was similar for both groups (DA + HC, 84% satisfied vs . DA only, 85%). Conclusion: These results suggest that watching the video DA improved patient knowledge and reduced decisional uncertainty about their spinal stenosis treatment choice. The addition of telephone coaching helped some patients choose a treatment more quickly; 6-month decisional outcomes were similar for both groups. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text